Physical and mechanical wood properties of two varieties of Pinus caribaea (Research, Society and Development, 2023)
This study aimed to characterize the properties of wood from Pinus caribaea var. hondurensis and Pinus caribaea var bahamensis, in 7-year-old individuals, in the municipality of Batatais, State of São Paulo, Brazil. For this, twelve trees of each species/variety were felled, and a 1 m long log was removed from the base of each tree. Samples were taken from the obtained logs to evaluate the physical-mechanical properties of the wood. It was verified that the woods of Pinus caribaea var. hondurensis and Pinus caribaea var. bahamensis do not differ significantly from each other for: Apparent density, basic density, compression parallel to the grain, shear parallel to grain, modulus of elasticity, volumetric shrinkage, anisotropy coefficient, radial shrinkage, and tangential shrinkage. The wood of the species/variety Pinus caribaea var. bahamensis showed a significantly higher modulus of rupture than the variety Pinus caribaea var. hondurensis. Regarding the use of wood from these species/variety, at a younger age, both showed potential use for different purposes. Since this initial assessment can be used as an indication of pre-selection of wood for the various segments of the timber industry, mainly for uses that do not have many restrictions in structural applications and dimensional variation.